Detection and Characterization of Carbapenemases in Enterobacterales With a New Rapid and Simplified Carbapenemase Detection Method Called rsCDM - Liao, Quanfeng; Yuan, Yu; Zhang, Weili; Deng, Jin; Wu, Siying; Liu, Ya; Xiao, Yuling; Kang, Mei (Frontiers in Microbiology, 2022)
Objective This study aimed to develop a new rapid and simplified carbapenemase detection method (rsCDM) for detection and characterization of carbapenemase with 3-aminophenylboronic acid (APBA), ethylenediaminetetraacetic acid (EDTA), and cloxacillin (CLO) β-lactamase inhibitors. Methods A panel of 182 carbapenem-resistant Enterobacterales (CRE) strains with blaKPC (88), blaNDM (60), blaIMP (10), blaVIM (3), blaOXA-181 (5), blaKPC, and blaNDM (7), porin changes in combination with an extended-spectrum β-lactamase (ESBL) (3) or AmpC hyper-production (6) and 43 carbapenem-susceptible Enterobacterales isolates were used to evaluate the performance of rsCDM and EDTA-carbapenem inactivation method (eCIM). Carbapenemase class was determined with specific inhibitors at 4, 6, and 18 h by rsCDM, and the difference between imipenem (IMI) and meropenem (MEM) disks was simultaneously compared. Results The sensitivity of rsCDM using IMI was 97.1% at the three time points, with a specificity of 100%, independent of the culture duration. Similar to IPM, MEM disk also showed high sensitivity (97.1%) and specificity (100%) at 6 h. And the sensitivity of eCIM was 95.4% and the specificity was 100%. Based on a decision algorithm, the characterization number of IMI and MEM in KPC-producing isolates was 88 vs. 87, metallo-β-lactamases (MBLs) was 73 vs. 72, KPC and NDM carbapenemase was 7 vs. 7 at 4 h, respectively. After 6 h, the category number changed insignificantly except for isolates with combined AmpC overproduction and porin changes, showing an increase in IMI (6) and MEM (2), and there was no difference in the results between 6 and 18 h for the two tablets. OXA-181-producing strains can’t be distinguished by rsCDM. For eCIM, the characterization number in KPC-, OXA- 181-, and MBLs-producing strains was 88, 5, and 72, but it failed to detect multi-enzyme-producing isolates (KPC and NDM). Conclusion rsCDM accurately discriminated carbapenemase within 4 h and could differentiate multi-enzyme (KPC and NDM) and AmpC in conjunction with porin changes strains. Hence, rsCDM represents a rapid, simple, easy readout, and accurate tool that can be used without any specialized equipment.